Autoestima y desempeño laboral de las enfermeras del Hospital Daniel Alcides Carrión-Callao - Huaman Gutierrez, Zoraida Judith (2020)
The objective was to determine the relationship between self-esteem and job performance of the nurses at the \Hospital Daniel Alcides Carrión". The method corresponds to a basic study, correlational level, quantitative approach, nonexperimental and cross-sectional design. The population was made up of 289 nurses, 165 of the total having been chosen in a non-probabilistic way. Data collection was done through two instruments with a reliability value of 0,922 and 0,965 respectively. For the bivariate analysis, the Chi-Square test was used, applying the simple correspondence analysis. The results indicated that there is a signicant relationship between self-esteem and job performance in the nurses of the Daniel Alcides Carrión hospital. (χ2 = 33, 898; p < 0,01), it was also shown that there is a signicant relationship between self-esteem and cognitive competence (χ2 = 24, 883; p < 0,01), also between self-esteem and attitudinal / social competences (χ2 = 25, 739; p < 0, 01) and between self-esteem and technical competence (χ2 = 18, 092; p < 0, 05). The study concludes that a good level of self-esteem signicantly improves job performance in nurses at the Daniel Alcides Carrión hospital.